2020
DOI: 10.1038/s41419-020-02988-8
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-catenin signaling pathway induces autophagy-mediated temozolomide-resistance in human glioblastoma

Abstract: Temozolomide (TMZ) is widely used for treating glioblastoma multiforme (GBM), however, the treatment of such brain tumors remains a challenge due to the development of resistance. Increasing studies have found that TMZ treatment could induce autophagy that may link to therapeutic resistance in GBM, but, the precise mechanisms are not fully understood. Understanding the molecular mechanisms underlying the response of GBM to chemotherapy is paramount for developing improved cancer therapeutics. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 55 publications
(82 reference statements)
4
59
0
Order By: Relevance
“…Consistent with these findings, activation of the canonical Wnt/β-catenin signaling cascade induces MGMT expression, and its inhibition augments the cytotoxic effects of TMZ [44]. Recently, it was shown that Wnt pathway may contribute to TMZ resistance through induction of autophagy [45] and that Wnt activation upon TMZ treatment is mediated by PI3K/Akt pathway [46].…”
Section: Discussionmentioning
confidence: 66%
“…Consistent with these findings, activation of the canonical Wnt/β-catenin signaling cascade induces MGMT expression, and its inhibition augments the cytotoxic effects of TMZ [44]. Recently, it was shown that Wnt pathway may contribute to TMZ resistance through induction of autophagy [45] and that Wnt activation upon TMZ treatment is mediated by PI3K/Akt pathway [46].…”
Section: Discussionmentioning
confidence: 66%
“…Meanwhile, based on the IC 50 value of si-CRNDE group in three cell lines (98.3 μM, 102.3 μM and 78.9 μM, respectively, Fig. 2 a) and referred to similar studies [ 28 , 29 ], we chose the TMZ concentration of 100 μM for subsequent experiments. Then, the effect of CRNDE expression on cell proliferation was assessed by clone formation assays in three cell lines treated with or without the treatment of TMZ at 100 μM for 72 h. The results revealed that the number of colonies was reduced in silence CRNDE group compared with control group without TMZ treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that TMZ-induced protective autophagy reduces ALDH expression, thereby contributing to the chemoresistance in glioma cells [146]. Similarly, Yun et al recently explained the role of the DOC-2/DAB2 interacting protein (DAB2IP), which is a member of the Ras-GTPase activating proteins in chemoresistance in glioblastoma cell lines [147]. DAB2IP enhanced the sensitivity of A172 and U373 cells to TMZ via suppressing the protective autophagy through downregulating ATG9B expression.…”
Section: Targeting Autophagy To Overcome Chemoresistance In Glioblastoma Cellsmentioning
confidence: 96%